A Novel SAVE Score to Stratify Decompensation Risk in Compensated Advanced Chronic Liver Disease (CHESS2102): An International Multicenter Cohort Study - Liu, Chuan; Cao, Zhujun; Yan, Huadong; Wong, Yu Jun; Xie, Qing; Hirooka, Masashi; Enomoto, Hirayuki; Kim, Tae Hyung; Hanafy, Amr Shaaban; Liu, Yanna; Huang, Yifei; Li, Xiaoguo; et al. (The American journal of gastroenterology, 2022)
In patients with compensated advanced chronic liver disease (cACLD), the invasive measurement of hepatic venous pressure gradient is the best predictor of hepatic decompensation. This study aimed at developing an alternative risk prediction model to provide a decompensation risk assessment in cACLD. Patients with cACLD were retrospectively included from 9 international centers within the Portal Hypertension Alliance in China (CHESS) network. Baseline variables from a Japanese cohort of 197 patients with cACLD were examined and fitted a Cox hazard regression model to develop a specific score for predicting hepatic decompensation. The novel score was validated in an external cohort (n = 770) from 5 centers in China, Singapore, Korea, and Egypt, and was further assessed for the ability of predicting clinically significant portal hypertension in a hepatic venous pressure gradient cohort (n = 285). In the derivation cohort, independent predictors of hepatic decompensation were identified including Stiffness of liver, Albumin, Varices, and platElets and fitted to develop the novel score, termed "SAVE" score. This score performed significantly better (all P < 0.05) than other assessed methods with a time-dependent receiver operating characteristic curve of 0.89 (95% confidence interval [CI]: 0.83-0.94) and 0.83 (95% CI: 0.73-0.92) in the derivation and validation cohorts, respectively. The decompensation risk was best stratified by the cutoff values at -6 and -4.5. The 5-year cumulative incidences of decompensation were 0%, 24.9%, and 69.0% in the low-risk, middle-risk, and high-risk groups, respectively ( P < 0.001). The SAVE score also accurately predicted clinically significant portal hypertension (AUC, 0.85 95% CI: 0.80-0.90). The SAVE score can be readily incorporated into clinical practice to accurately predict the individual risk of hepatic decompensation in cACLD.